(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
In the rapidly changing global educational environment, the competence of primary school teachers has become a fundamental determinant of educational quality, innovation, and national development. This study examines the conceptual foundations, theoretical models, and practical dimensions of teacher competence within the context of modern educational reforms, particularly emphasizing the transformation of pedagogical culture in developing countries. The research adopts a multidisciplinary approach that integrates psychology, pedagogy, linguistics, and digital literacy perspectives to explore how competencies are structured, developed, and assessed in early childhood and primary education. Using a mixed-method framework combining document analysis, theoretical synthesis, and comparative case studies, the paper investigates cognitive, operational, ethical, and communicative components of competence. Findings reveal that modern teacher competence encompasses not only knowledge and skill mastery but also adaptive thinking, socio-emotional intelligence, and digital pedagogical literacy, which collectively define the teacher’s capacity for innovative and inclusive classroom practices. The study concludes that primary teacher competence must be continuously renewed through reflective practice, professional development, and institutional support, ensuring alignment with 21st-century educational paradigms and lifelong learning objectives.